Collaborative Learning Approach to Enhancing College Student's Contextual Knowledge of the Fundamentals of Accounting - Norkhadirah, Anuar (2011)
This study highlighted the perceptions of students had when taught Fundamentals of Accounting using the collaborative approach. Little attention had been given to whether students perceived these strategies as effective and are able to apply them to help them in learning the accounting course. The study focuses on 27 college students who are pursuing a diploma in accounting. The results from the study indicated that students positive perceptions determine the effectiveness of the collaborative activities for them and there were references in their results to contextual learning.The implications from the study suggest that the effectiveness of collaborative learning could be adopted more broadly to enhance contextual knowledge of the Fundamentals of Accounting among students.